Agkistrodon ameliorates pain response and prevents cartilage degradation in monosodium iodoacetate-induced osteoarthritic rats by inhibiting chondrocyte hypertrophy and apoptosis. (1st March 2019) - Wang, Caiwei; Yan, Li; Yan, Bo; Zhou, Li; Sun, Wan; Yu, Lingying; Liu, Fucun; Du, Wenxi; Yu, Guangping; Hu, Zhengyan; Yuan, Qiang; Xiao, Luwei; et al.
Abstract: Ethnopharmacological relevance: Osteoarthritis (OA), characterized by joint pain and cartilage degradation, is the most common form of joint disease worldwide but with no satisfactory therapy available. The ethanol extract of Agkistrodon acutus (EAA) has been widely used as a traditional Chinese medicine (TCM) for the treatment of arthralgia and inflammatory diseases, but there is no report regarding its efficacy on OA to date. Here, we determined the effects of EAA on the pain behavior and cartilage degradation in vivo and clarified its target genes and proteins associated with chondrocyte hypertrophy and apoptosis in vitro. Materials and methods: In vivo OA model was established by intra-articular injection (1.5 mg) of monosodium iodoacetate (MIA) into rats and weekly treated by intra-articular administration of EAA at a dose range from 0.3 to 0.9 g/kg for four weeks. The pain behavior parameters, thermal withdrawal latency (TWL) and mechanical withdrawal threshold (MWT) were tested before and after the treatment. Then histopathologic, immunohistochemical and TUNEL analyses of the articular cartilage were conducted, followed by Mankin′s scoring. In vitro, the effects of EAA on chondrocytes were evaluated via assays of cell viability, immunofluorescence, real time PCR, and Western blot. UPLC-MS was applied to determine the chemical composition of EAA. Results: The animal data showed that EEA not only attenuated the pain hypersensitivity but also blocked the cartilage degeneration by improving chondrocyte survival and suppressing chondrocyte apoptosis at a dose-dependent manner in OA rats. Furthermore, EAA remarkably restored the abnormal expression of collagen type II (Col2) and matrix metalloproteinase-13 (MMP13) in cartilage of OA rats. The cellular data showed that EAA significantly increased the cell viability of chondrocytes against OA-like damage and restored the abnormal expressions of Col2 and MMP13 in damaged chondrocytes. The molecular data showed that EAA significantly restored the abnormal mRNA expressions of Col2, Col10, MMP2 and MMP13 as well as the abnormal protein expressions of MMP13, PARP (total and cleaved) in chondrocytes under pathological condition. UPLC-MS analysis showed the known main components of EAA, including amino acides (glycine, L -aspartic acid, L -glutamic acid, and L-hydroxyproline), nucleoside (uridine), purines (xanthine and hypoxanthine), and pyrimidine (uracil). Conclusions: Our data demonstrate that EAA exerts antinociceptive and chondroprotective effects on OA through suppressing chondrocyte hypertrophy and apoptosis with restoration of the molecular expressions of anabolism and catabolism in chondrocytes. It provides a promising TCM candidate of novel agent for OA therapy. Graphical abstract: